The Influence of Forming a General World View in Family Relations on Child Education - Sharipova Surayyo (Genius Journals, 2022)
This article discusses the formation of a universal worldview in family relations and the influence of a healthy family environment on child upbringing, psychological features of child upbringing in the family
Keywords: family relations; child upbringing in the family; father; mother